Validation of the Nepali version of beck anxiety inventory - Kohrt, B A; Koirala, N R; Sharma, V D; Nepal, M K (Journal of Institute of Medicine Nepal, 2024)
This study validates a Nepali version of the Beck Anxiety Inventory (BAI). The instrument was compared against a gold standard diagnosis of generalized anxiety. The diagnosis of Generalized Anxiety Disorder (GAD) was made according to the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition. GAD subjects were selected both from outpatients at Tribhuvan University Teaching Hospital and a rural sample from Jumla. Healthy (non-psychiatric diagnosis) cases were taken from a community sample in Jumla; their “healthy” status was obtained by achieving a score less than 2 on the Nepali General Health Questionnaire-12. This study identifies acceptable sensitivity and specificity ranges for the measure. A cut-off of 13/14 for the BAI provides sensitivity of 0.91 and specificity of 0.89. Reliability for the BAI is comparable to most studies in Western countries (0.89). A factor analysis of the BAI evokes four factors. A number of items reduce the validity and internal reliability of this measure. Somatic items poorly distinguish psychiatric cases; this may be due to high burden of physical illness in rural Nepal. Overall, the BAI appears to be a good instrument for clinical and research use in Nepal.